Project-Based Learning Based on Mastery Learning to Improve Continuous Numeracy Literacy in High School Students: Literature Review - Andriani, Dwi Nila; Prasetya Wibawa, Ramadhan; Firtriawati, Dewi; Winanda, Intan; Saputri, Meilani Alda (LP. Ma'arif Janggan Magetan, 2025)
The low numeracy literacy of high school students is an important challenge in 21st century education, especially in the implementation of the Independent Curriculum which emphasizes meaningful and sustainable learning. This study aims to explore the potential of integrating Project Based Learning (PjBL) and Mastery Learning as an innovative approach to improve students' numeracy literacy. The research was conducted through a narrative literature study by searching through articles from Google Scholar, Scopus, ERIC, and DOAJ databases. The inclusion criteria include articles published between 2013–2024, relevant to the topic, and in the form of scientific journals or accredited proceedings. The results of the study show that PjBL provides a contextual learning experience that improves the understanding of numerical concepts applicatively. Meanwhile, Mastery Learning ensures the completeness of each numeracy indicator through a gradual and evaluative approach. The integration of these two approaches creates active, structured, and adaptive learning to students' learning needs. The implications of these findings show that an integrative approach can support the transformation of numeracy learning in the context of the Independent Curriculum. The study also recommends the development of teaching tools and teacher training to effectively implement integrative models. In conclusion, the integration of PjBL and Mastery Learning is a promising strategy in improving numeracy literacy in a sustainable manner at the secondary education level.